The effectiveness of laughter yoga to improve sleep quality in cancer patients during COVID-19 pandemic - Werdani, Yesiana Dwi Wahyu (Universitas Udayana, 2022)
Background and purpose: The COVID-19 pandemic triggered a high-stress situation and disrupted sleep quality in cancer patients. Laughter yoga is a method that suggested to improve sleep quality. The purpose of this study was to assess the effectiveness of laughter yoga to improve sleep quality of cancer patients during the pandemic. Methods: This was a quasi-experimental design with a non-equivalent control group approach. The study was conducted at the Indonesian Cancer Foundation, East Java Surabaya branch, in June 202, involved 20 people in each intervention and control group. The instrument used was Pittsburg Sleep Quality Index (PSQI), with lower scores reflect better sleep quality. Laughter yoga intervention was given to the intervention group for four weeks, twice a week, and 20 minutes each meeting while the control group performed daily routine activities. Data was analysed with Paired t-test for pre and post intervention, and Independent Sample t-test for comparing both groups. Results: The intervention group shows a decrease in the global PSQI score (from 10.15+2.18 to 7.55+1.87) with p< 0.001, while in control group, there was an increased score (from 10.05+1.46 to 10.10+1.44) with p=0.841. The intervention group showed a decrease in the average score on the global and all of the components PSQI score, indicating a better sleep quality. Meanwhile, in the control group, the average global sleep quality score almost the same, and no significant decrease in all components. Laughter yoga was effective in improving the sleep quality of cancer patients during the pandemic. Conclusion: Laughter yoga is effective to improve sleep quality. This technique can be routinely practice to improve relaxation and stimulate improvements in sleep quality in all components.